THE BEGINNING AND EARLY YEARS OF RADIOCARBON DATING IN RUSSIA: LABORATORIES AND PERSONALITIES. Issue 3 (25th June 2022) - Kuzmin, Yaroslav V; Burova, Natalia D; Zazovskaya, Elya P; Zaretskaya, Nataliya E; Savinetsky, Arkady B; Khasanov, Bulat F
ABSTRACT: We present an overview of the beginning and early years of radiocarbon dating in Russia. Achievements of several major scholars in this field from Leningrad (St. Petersburg), Moscow and Novosibirsk are briefly described. The existing and closed Russian laboratories are also mentioned.